"A Peaceful Happy Easter" - Truman State University, Pickler Memorial Library Special Collections, University Archives (Owner, Digitizing Technician) (1912)
Easter postcard with a poem and depiction of Jesus, sheep, and a cross; addressed to Mrs. F. M. Anderson from Jane and J. R. E.; postmarked April 4, 1912.